2018
DOI: 10.1007/s11060-017-2733-0
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment after biodegradable BCNU wafer implantation: special consideration of immune system

Abstract: Biomaterials to treat cancers hold therapeutic potential; however, their translation to bedside treatment requires further study. The carmustine (1,3-bis (2-chloroethyl)-1-nitrosourea; BCNU) wafer, a biodegradable polymer, currently is the only drug that is able to be placed at the surgical site to treat malignant tumors. However, how this wafer affects the surrounding tumor microenvironment is not well understood to date. We retrospectively reviewed all patients with glioblastoma treated with and without BCNU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In past studies, a large number of oncogenes have been identified to be closely related to the prognosis, radiotherapy resistance and metastasis of NPC, but the regulation of the immunological characteristics of NPC cells by these oncogenes has rarely been reported [20,21]. Studies show that tumor tissues are infiltrated with a large number of natural and acquired immune cells, such as CD4 þ T cells, CD8 þ T cells, NK cells, macrophages, mast cells, and dendritic cells [22,23]. The distant metastasis of tumor cells requires evasion of tumor cells from surveillance by immune cells, and the roles of oncogenes in this process still need further studies.…”
Section: Resultsmentioning
confidence: 99%
“…In past studies, a large number of oncogenes have been identified to be closely related to the prognosis, radiotherapy resistance and metastasis of NPC, but the regulation of the immunological characteristics of NPC cells by these oncogenes has rarely been reported [20,21]. Studies show that tumor tissues are infiltrated with a large number of natural and acquired immune cells, such as CD4 þ T cells, CD8 þ T cells, NK cells, macrophages, mast cells, and dendritic cells [22,23]. The distant metastasis of tumor cells requires evasion of tumor cells from surveillance by immune cells, and the roles of oncogenes in this process still need further studies.…”
Section: Resultsmentioning
confidence: 99%
“…[21,22] High-dose intravenous carmustine (800/m 2 ) has been associated with retinal artery narrowing and obstruction. [31] Carmustine has also been shown to induce vasospasm in rabbit models through inhibition of glutathione reductase activity, indicating presence of local inflammatory reactions secondary to the foreign wafers. [30] In addition, Shibahara et al demonstrated a significant increase in surrounding immune cells with BCNU implantation in GBM patients and augmentation of inflammatory response in nearby tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Current trends in drug delivery aim to bypass, breach, and negotiate the BBB. Between them, the use of hyperosmotic solutions [56], FUS [155], biodegradable implants [156], and CED [157] are extensively used and/or investigated in the clinic for their safety and efficacy. On the other hand, to our knowledge, only one model of targeted nanoparticle is under investigation in humans for the treatment of GBM [158].…”
Section: Discussionmentioning
confidence: 99%